2014
DOI: 10.3389/fpls.2014.00689
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol oxidase as a biochemical seed defense mechanism

Abstract: Seed dormancy and resistance to decay are fundamental survival strategies, which allow a population of seeds to germinate over long periods of time. Seeds have physical, chemical, and biological defense mechanisms that protect their food reserves from decay-inducing organisms and herbivores. Here, we hypothesize that seeds also possess enzyme-based biochemical defenses, based on induction of the plant defense enzyme, polyphenol oxidase (PPO), when wild oat (Avena fatua L.) caryopses and seeds were challenged w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
62
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 74 publications
2
62
0
6
Order By: Relevance
“…Quinones and other reactive intermediates (e.g., 5,6-dihydroxyindole) are more toxic to herbivores than the original phenolic substrates and may kill microbial pathogens and parasitoids directly [72]. Many PPOs cooperate with peroxidases (PODs; EC 1.11.1.7) [73] and have diverse and overlapping physiological functions in plants, which include involvement in redox metabolism, responses to wound healing, defense against pathogens or insects, synthesis of lignin and suberin, and cross-linking of cell wall components [74,75].…”
Section: Polyphenol Oxidase (Ppo) Properties and Physiological Functionsmentioning
confidence: 99%
“…Quinones and other reactive intermediates (e.g., 5,6-dihydroxyindole) are more toxic to herbivores than the original phenolic substrates and may kill microbial pathogens and parasitoids directly [72]. Many PPOs cooperate with peroxidases (PODs; EC 1.11.1.7) [73] and have diverse and overlapping physiological functions in plants, which include involvement in redox metabolism, responses to wound healing, defense against pathogens or insects, synthesis of lignin and suberin, and cross-linking of cell wall components [74,75].…”
Section: Polyphenol Oxidase (Ppo) Properties and Physiological Functionsmentioning
confidence: 99%
“…Accordingly, wheat bran was found to contain multiple plant defense-related proteins including oxalate oxidase (OXO), peroxidase (POX), and polyphenol oxidase (PPO) whose activities were highest in the outer layer [41]. Also, when oat DU was incubated with Fusarium avenaceum strain F.a.1, polyphenol oxidase (PPO) was induced in the whole DU as well as in the dissected parts, namely the dead, non-living hulls (lemma and palea) and the caryopses [42].…”
Section: Doees Release Hundreds Of Proteins Upon Hydrationmentioning
confidence: 99%
“…The authors suggested that the induction of PPO in the non-living hulls, although surprising, could have resulted from latent forms of PPO that are activated following challenge with F.a.1 [42].…”
Section: Doees Release Hundreds Of Proteins Upon Hydrationmentioning
confidence: 99%
“…POXs are multifunctional redox enzymes [20][21] that regulate biochemical processes such as the cross-linking of cell wall components, the production of secondary metabolites and key reactions in the hypersensitive response [21]. PPOs have been characterized as a common component of the plant innate immune response [22] and are responsible for catalyzing the oxidation of monophenols and/or o-diphenols to o-diquinones. Through secondary reactions, o-diquinones can promote quinone toxicity and confer resistance against pathogens [23][24].…”
Section: Introductionmentioning
confidence: 99%